2013
DOI: 10.1088/0029-5515/53/6/066001
|View full text |Cite
|
Sign up to set email alerts
|

Power requirements for electron cyclotron current drive and ion cyclotron resonance heating for sawtooth control in ITER

Abstract: Abstract.13MW of electron cyclotron current drive (ECCD) power deposited inside the q = 1 surface is likely to reduce the sawtooth period in ITER baseline scenario below the level empirically predicted to trigger neo-classical tearing modes (NTMs). However, since the ECCD control scheme is solely predicated upon changing the local magnetic shear, it is prudent to plan to use a complementary scheme which directly decreases the potential energy of the kink mode in order to reduce the sawtooth period. In the even… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…A need for control of the sawtooth instability is also anticipated in ITER, in order to avoid long period sawteeth with large amplitude crashes that could trigger an NTM instability [23], and several schemes using ECCD or ICRF heating have been proposed [24]. Recent JET experiments have shown that the sawtooth period can be controlled with low field side ICRF heating (as will be available in ITER) near the q=1 surface [25], and that sawtooth pacing can be achieved with modulated central ion cyclotron heating [26], a method that is less sensitive to the deposition location.…”
Section: Plasma Configuration Controlmentioning
confidence: 99%
“…A need for control of the sawtooth instability is also anticipated in ITER, in order to avoid long period sawteeth with large amplitude crashes that could trigger an NTM instability [23], and several schemes using ECCD or ICRF heating have been proposed [24]. Recent JET experiments have shown that the sawtooth period can be controlled with low field side ICRF heating (as will be available in ITER) near the q=1 surface [25], and that sawtooth pacing can be achieved with modulated central ion cyclotron heating [26], a method that is less sensitive to the deposition location.…”
Section: Plasma Configuration Controlmentioning
confidence: 99%
“…We see that the value of Q cannot be deduced precisely only from heat demand considerations, since the kinetic profiles and the fusion power are not very sensitive to the amount of external heating power during the flat top phase. The required maximum injected external power depends more on the access of the H-mode during start up and the needed current drive for different scenarios [17,18] and the latter may be a more crucial constraint for the determination of Q.…”
Section: Consequences For Itermentioning
confidence: 99%
“…5) and sawteeth. The design work is supported by extensive simulations for the various tasks and by extrapolation from current experiments to ITER [53][54][55]. Still uncertainties remain.…”
Section: The Iter Ecrh Systemsmentioning
confidence: 99%